Media Buku Ilustrasi Permainan Tradisional Congklak Di Indonesia - Mutiara Azmi; Carolus Astabrata (Penerbit dan Percetakan, CV. Picmotiv, 2025)
The traditional game of congklak, which has existed for generations, is an important part of Indonesia’s cultural heritage that must be preserved, despite the dominance of digital games today. The aim of this study is to create an illustrated book using pop-up techniques with congklak as its central theme. This book serves as an interactive and enjoyable educational medium. The research method employed is a qualitative approach, including observation of pop-up books, interviews with cultural preservationists and pop-up book illustrators, as well as a literature review of congklak variations from different regions of Indonesia. The book aims to introduce children to the diversity of congklak games across the country, explain how the game is played, and encourage them to understand the positive values embedded in the game. Through a visually engaging approach, featuring bright colors, simple character designs, and child-friendly fonts, this book functions not only as a source of entertainment but also as a cultural preservation tool. It helps shape children's character through the values of sportsmanship, togetherness, and honesty found in the game of congklak. It is hoped that this pop-up book will serve as a starting point for cultural preservation in a more modern and educational way